Empowering village potential towards intelligent communities in implementing clean and healthy lifestyles in Damuli Kebun village South Kualuh subdistrict North Labuhanbatu Regency - Gulo, Hubari; Tinambunan, Ayurut Desica; Sitorus, Emelia Anggraini; Hutasoit, Ismail (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
PHBS (Clean and Healthy Lifestyle) is all health behaviors that are carried out due to personal awareness so that the family and all members are able to help themselves in the health field and have an active role in community activities. Clean hygiene behavior is basically an effort to transmit experiences about healthy lifestyles through individuals, groups or the wider community with channels of communication as a medium for sharing information. The main objective of the PHBS movement is to improve the quality of health through an awareness process that is the beginning of the contribution of individuals - individuals in living clean and healthy daily life behaviors. The most important benefit of PHBS is the creation of a community that is health conscious and has the provision of knowledge and awareness to live life behaviors that maintain hygiene and meet health standards. Through this program, we educate both theory and practice directly to the community of Damuli Kebun Village on the importance of a Clean and Healthy Lifestyle in daily activities.